Characterization of T-Circles and Their Formation Reveal Similarities to Agrobacterium T-DNA Integration Patterns - Gelvin, Stanton B.; Singer, Kamy; Lee, Lan-Ying; Yuan, Jing (Frontiers in Plant Science, 2022)
Agrobacterium transfers T-DNA to plants where it may integrate into the genome. Non-homologous end-joining (NHEJ) has been invoked as the mechanism of T-DNA integration, but the role of various NHEJ proteins remains controversial. Genetic evidence for the role of NHEJ in T-DNA integration has yielded conflicting results. We propose to investigate the formation of T-circles as a proxy for understanding T-DNA integration. T-circles are circular double-strand T-DNA molecules, joined at their left (LB) and right (RB) border regions, formed in plants. We characterized LB-RB junction regions from hundreds of T-circles formed in Nicotiana benthamiana or Arabidopsis thaliana. These junctions resembled T-DNA/plant DNA junctions found in integrated T-DNA: Among complex T-circles composed of multiple T-DNA molecules, RB-RB/LB-LB junctions predominated over RB-LB junctions; deletions at the LB were more frequent and extensive than those at the RB; microhomology was frequently used at junction sites; and filler DNA, from the plant genome or various Agrobacterium replicons, was often present between the borders. Ku80 was not required for efficient T-circle formation, and a VirD2  mutation affected T-circle formation and T-DNA integration similarly. We suggest that investigating the formation of T-circles may serve as a surrogate for understanding T-DNA integration.